Optimizing Supply Chain Management: A Systematic Review of Logistics 4.0 for Intelligent and Sustainable Transformation - Llocclla-Salazar, Henrry; Puma-Flores, Ruth Zulema; Alvarado-Silva, Carlos Alexis (LACCEI, 2025)
The constant global technological evolution has driven the integration of tools such as digitalization and automation into industrial processes, marking the advent of Industry 4.0. In this context, this review on Logistics 4.0 aims to identify how these technologies enhance supply chain management efficiency, enabling companies to reduce costs, improve quality, and optimize inventory management. Method: This study is based on a Systematic Literature Review (SLR) using the Scopus database as the primary source. The PRISMA and PICO methods were employed to carry out a structured and rigorous process for identifying, selecting, and analyzing relevant studies. After applying inclusion and exclusion criteria, 42 articles were selected from an initial total of 2416 for detailed analysis. Results: The analysis revealed that technologies such as the Internet of Things (IoT), automated guided vehicles (AGV), artificial intelligence (AI), and Big Data have significantly contributed to optimizing management processes in Logistics 4.0. These tools have proven effective in improving operational and strategic efficiency in companies. Conclusion: The proper implementation of technologies in Logistics 4.0 management significantly improves processes by delivering higher quality products and services, reducing costs, and consequently increasing business profitability.